The Effectiveness of Village Heads as Mediators in Land Dispute Resolution: An Empirical Juridical Study in Pasilian Village, Tangerang Regency - Abdulatip Abdulatip; Muh Nasir; Rasman Habeahan (BULETIN ADALAH, 2026)
Land disputes remain a persistent challenge in rural Indonesia, often threatening social cohesion and local development. While formal litigation offers a legally binding resolution, its cost, complexity, and length frequently deter village communities. Consequently, alternative dispute resolution through mediation has emerged as a preferred mechanism, with the Village Head functioning as a key mediator due to his or her formal authority and social legitimacy. This study examines the implementation and effectiveness of the Village Head's mediating role in land disputes in Pasilian Village, Kronjo District, Tangerang Regency. Employing a socio-legal or empirical-normative research methodology, the study combines analysis of statutory regulations with empirical data obtained through in-depth interviews, direct observation, and documentary analysis. The findings reveal that the Village Head performs multiple functions: as a facilitator of dialogue, a neutral intermediary, and a guardian of local wisdom. However, the effectiveness of this role is constrained by several factors, including limited legal knowledge regarding agrarian law and mediation techniques, the absence of standardised procedural guidelines, weak administrative documentation of land rights, and the potential for bias arising from kinship ties or local political interests. Furthermore, mediation outcomes lack formal executorial force, undermining legal certainty. The study concludes that while the Village Head's mediation offers significant advantages in terms of speed, cost, and social harmony, its sustainability requires institutional reinforcement through capacity-building programmes, clearer regulatory frameworks, and enhanced coordination with land agencies. Recommendations include the development of standard operating procedures for village-level mediation, systematic training for Village Heads in agrarian law and conflict resolution, and improved land administration systems to prevent future disputes. Keywords: Village Head; mediation; land dispute; socio-legal study; alternative dispute resolution